High speed end milling of single crystal silicon wafer - Amin, A. K. M. Nurul; Musa, Mohd Dali (LAP Lambert Academic Publishing, 2011)
Presently, silicon is the most important semiconducting material used in the electronic industry. Silicon has also found application in energy and mechanical application such as electro-optics and micro-electro mechanical system (MEMS) devices. The process of machining silicon requires high quality surface finish and is generally achieved through processes such as grinding, polishing and lapping. In this experimental work, high speed end-milling has been suggested as an alternative to the traditional finishing process. There are a number of technological barriers which high speed end-milling must overcome for it to be able to machine silicon. Crack free surface and continuous chip should be form during machining which can only be obtained in ductile regime machining. In ductile regime machining, the surface is smooth, where as in the brittle regime, there are surface cracks. Ductile regime machining of silicon is hard to obtain due to the brittle properties of silicon and hardness of tool materials. Prior research shows that ductile mode of machining is possible under controlled machining conditions. Various parameters such as cutting speed, depth of cut and rake angle show effect on ductile mode machining of silicon. In this perspective, obtaining the right machining parameters to machine silicon plays an important role to obtain ductile mode machining.